Formal and legal framework for the implementation, development and functioning of electromobility in Poland and the European Union - Kucharski, Adam (Management and Administration Journal, 2025)
One of the key elements for achieving the EU's climate goals is the decarbonization of transport. However, in order to achieve the expected results, the European transport sector must undergo a transformation. One of the directions being considered is the use of electric vehicles. The number of documents affecting the formal and legal operation of electromobility is large. The purpose of the article is to systematize and present selected legal acts that significantly impact the implementation, development and operation of electromobility in the EU and Poland. These issues are addressed within the broader context of the interrelationships among electromobility, environmental protection, infrastructure development, and energy. The analysis confirmed the existence of numerous issues that require further elucidation and regulation in a sustainable Europe.